Кримінальне законодавство України у контексті розвитку конституційних засад - Кваша, О.; Пархоменко, Н.; Kvasha, О.; Parkhomenko, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті обґрунтовано, що у галузі кримінального права конституційні засади набувають специфіки, яка обумовлюється особливостями правового регулювання та охорони суспільних відносин. Зважаючи на велике не лише теоретичне, але і практичне значення конституційних засад кримінального права, особливої уваги потребує питання доцільності закріплення в КК України окремої статті чи розділу, у якому б комплексно визначались основні із таких засад. Найбільш перспективним у цьому сенсі є доктринальне дослідження значення конституційних засад розвитку кримінального права України. The article substantiates that in the area of criminal law the constitutional principles acquire specific features. The process is caused by the peculiarities of the legal regulation and protection of social relations. The importance of securing constitutional provisions in criminal law is largely due to the haphazard process of introducing changesinto the Criminal Code of Ukraine. The importance is placed on the conditions that would make the process of constitualization of the criminal law more effective. It was concluded that only a systematic analysis of criminal legislative issues and manifestations of the importance of the constitutional principles enforcement can provide the objectiveness of the conclusions as to its future trends of improvement. In view of the great theoretical and practical importance of the constitutional principles for the criminal law, special attention should be paid to the rationale for including a separate article or chapter into the Criminal Code of Ukraine, which would define the main integrating constitutional principles of criminal legislation .
Criminal Legislation of Ukraine in the Context of Constitutional Principles Development
Keywords: Конституція України; кримінальне законодавство; засади; принципи; система; Constitution of Ukraine; criminal law; foundations; principles; system